Recent progress in the use of Co-, Ni- and Ni/Co-MOF as electrode materials for supercapacitors - Mertsoy, Esra Yilmaz; Yasa, Sezgin; Gencten, Metin (ELSEVIER SCIENCE SA, 2025)
Supercapacitors are emerging as critical energy storage systems due to their high power density, long cycle life, and rapid charge-discharge capabilities. To meet the growing demand for devices with both high power and high energy densities, the development of advanced electrode materials remains a key research focus. Among various candidates, metal-organic frameworks (MOFs) have attracted significant attention as electrode materials because of their large surface area and highly porous structures. This review highlights recent progress on pristine Ni-and Co-MOFs, bimetallic Ni/Co-MOFs, their composites, and MOF-derived materials. The electrochemical performances and structural advantages of these systems are discussed to provide an up-to-date overview of their potential as supercapacitor electrodes. Given the rapid progress and the substantial body of research on Ni-and Co-MOF-based electrodes, this review consolidates recent findings and provides a clear perspective on current research directions, while emphasizing existing knowledge gaps and future opportunities in the field. Future challenges and research directions, particularly regarding supercapacitive performance and structural stability, are also addressed. The insights summarized here underline the potential of Ni-and Co-MOF-based systems for next-generation supercapacitors and large-scale energy storage applications.
Keywords: MOF; Supercapacitor; Nickel; Cobalt; Electrochemistry; METAL-ORGANIC FRAMEWORKS; POROUS CARBON MATERIALS; COMPOSITES; CONSTRUCTION; CHALLENGES; DESIGN; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering